The Effects of Public Participation on Local Economic Development in South African Municipalities - KGOBE, France Khutso Lavhelani; MABEBA, Selaelo John; MAMOKHERE, John (International Journal of Environmental, Sustainability, and Social Science, 2023)
In recent years, the concept of Local Economic Development (LED) has gained prominence to enhance the economic well-being of communities at the grassroots level. In South Africa, a country marked by a history of inequality and spatial disparities, fostering LED has become crucial. Public participation is crucial in shaping the LED trajectory in South African municipalities. By analyzing existing literature, this article underscores the importance of inclusive and meaningful engagement of citizens in the process of LED, highlighting its benefits and challenges. In other words, this article explores the effects of public participation on LED in South African municipalities. This study adopted a qualitative research methodology. The study specifically reviewed secondary data to understand the effects of public participation on local economic development in South African municipalities. In conclusion, to address public participation challenges in LED, local government should design participation processes that actively involve all segments of the population, especially marginalized and historically disadvantaged groups.